PEMANFAATAN LIMBAH PERTANIAN TONGKOL JAGUNG SEBAGAI BAHAN BAKU PEMBUATAN BRIKET DI NAGARI BUKIK SIKUMPA KABUPATEN LIMA PULUH KOTA - Zulkarnaini Zulkarnaini; Khasman Khasman; Chyntia Dhiya Ulhaq (Jurnal Hilirisasi IPTEKS, 2023)
This activity aims to provide a solution for the people of Nagari Bukik Sikumpa, Lareh Sago Halaban Sub-district, Lima Puluh Kota Regency, in dealing with the abundance of corn cobs resulting from agricultural waste. These cobs can be raw materials to produce briquette charcoal, which has commercial value and is an eco-friendly alternative energy source. The methodology employed was to conduct a socialization effort that introduced the concept of briquette charcoal, accompanied by a demonstration of briquette charcoal production. The aim was to utilize agricultural waste, specifically corn cob, and turn it into an environmentally friendly and commercially viable product. Additionally, posters were put up to support information dissemination relating to briquettes within the community of Nagari Bukik Sikumpa. Based on the conducted socialization activities, the community's enthusiasm was evident through the attendance of 160 people and numerous questions asked during the event. The outcome of this activity is in the form of briquette charcoal that can sustain flame for approximately 1 hour and 7 minutes per piece of briquette without emitting carbon during the burning process. With the implementation of this activity, it can be concluded that the community has understood how to process agricultural waste from corn cobs, which are typically discarded as they are, into briquettes that have commercial value and serve as an eco-friendly alternative energy source. Corn cob briquettes could provide a promising business opportunity for the local community due to the abundance of agricultural waste in the form of corn cobs, which is not utilized in the local region. Corn cob briquettes have gained significant interest among the locals as they can be made from easily obtainable materials.